Medicinal plants and the teaching of Natural Sciences (Revista Contexto & Educação, 2023)
This work aimed to arouse students' interest in chemistry, through the interaction between popular, scientific and school knowledge about medicinal plants in the teaching of Natural Sciences. Two theoretical and experimental classes were prepared on medicinal plants and the study of phenolic substances. Classes were held with ninth grade students from a public school in the city of São Gonçalo/RJ, in an urban area. In the first class, a questionnaire was applied and information was obtained about medicinal plants, their use, their name and their method of preparation, then concepts about medicinal plants were introduced and the concept of natural and contraindicated were discussed. In the second class, through a questionnaire, the students were able to evaluate their own learning and the efficiency of the method. The activities developed provided an opportunity to raise awareness among students about the presence of chemical substances in medicinal plants, and concepts of Chemistry, Biology and Physics. The methodology can be applied in the elaboration of classes and in the continuing education of teachers.
Keywords: popular knowledge; ethnobotany; teaching methods; chemistry